Indeks Kepuasan Masyarakat di Kantor Lurah Detusoko - Dorotea Riwu; Antonius Philipus Kurniawan; Yosef Tonce (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aims to assess the services provided by the Detusoko Village Office based on public satisfaction Index. The research included participants who had received services at the Detusoko Village Office in 2023. The nonprobability sampling technique, specifically incidental sampling, was used for selecting the subjects. The primary and secondary data were used as the sources of information. Data collection methods included questionnaires, document studies, and interviews. The validity test used the Pearson Product Moment formula, and the reliability test used the Cronbach’s Alpha formula. The results revealed that the Public Satisfaction Index for the Detusoko Village Office services was 71.41, categorizing it as “Less Good”